Applications of air photo interpretation techniques in the Langebaan area, S. Africa - Jarman, Margaret Louise (Department of Biological Sciences, 2017)
A fairly extensive introduction to the theory behind the use of remote sensing products for vegetation survey work is given. This includes the particular benefits of colour air photographs, the relationship between scale of survey and scale of mapping and remote sensing products, and more information about the 'semi-detailed' level of survey operation. The latter is the category of survey which the vegetation survey of the Langebaan area, South Africa, falls into. The importance of the timing of photography in the usefulness of air photographs in vegetation survey work is also emphasised. The particular example of the semi-detailed survey of the vegetation of the Langebaan Area using colour serial photographs of Job 195 was then used in describing the Phases of operation involved. Phase I is essentially the planning stage, Phase II the operational stage, divided into 5 separate sections of operation, and Phase III involves the final mapping and report compilation. Reference to the results is given, as is a short discussion on the merits of air photographic techniques.